Menganalisis Permasalahan Keterlambatan Pembayaran Pinjaman Anggota di Koperasi Bona Mandiri Jaya Abadi - Damanik, Dwi Azri; Perkasa, Ripho Delzy (As-Syirkah: Islamic Economic & Financial Journal, 2023)
Cooperatives are organizations launched and supported by the government with the aim that these organizations are able to improve people’s welfare through increasing per capita income for both members and non-members. The spread of cooperatives in cities and districts in Indonesia. The approach used is descriptive by interviewing informants in depth. The data sources used in this research are primary data and secondary data. The systems and procedures for implementing savings and loans at the Bona Mandiri Jaya Cooperative have not been carried out in accordance with predetermined procedures, including regarding member registration procedures, member deposit procedures, member loan procedures, loan installment procedures for purchasing goods, savings and loan documents, deposit requirements, loan requirements, loan patterns and deposit conditions can be taken, all the procedures that have been set for the cooperative have been going well and are in accordance with the theory and the law that applies to cooperatives.